ANALISIS FAKTOR – FAKTOR YANG BERPENGARUH TERHADAP KECENDERUNGAN FINANCIAL STATEMENT FRAUD DALAM PERSPEKTIF FRAUD TRIANGLE (Studi Empiris Pada Perusahaan Yang Terdaftar Di BEI Periode 2009-2013) - Muhammad Nauval; Gugus Irianto (Jurnal Ilmiah Mahasiswa FEB, 2014)
This study aimed to determine the factors that affect the financial statement fraud tendency in the perspective of fraud triangle as the independent variable which was proxied through ACHANGE, LEV, ROA, BDOUT, INVS, and AUDCHANGE. The samples were the companies listed on the Stock Exchange in the period 2009  - 2013 are classified into companies that tend to commit fraud and the company did not commit fraud. Companies that tend to commit fraud are determined based on the sanctions list obtained from the Indonesia Financial Services Authority related to the violation of the regulations of VIII.G.7 by Bapepam-LK regarding the presentation and disclosure of financial statements of listed companies or public companies. Based on a purposive sampling technique used, there were 18 companies that commit violation and 35 companies that did not commit violation. The effect between the factors in fraud triangle perspective against the tendency of financial statement fraud were  analyzed using logistic regression analysis. Based on the results of data analysis, it can be concluded that the proxy of ROA, INVS, and AUDCHANGE has a significant effect on the tendency of financial statement fraud, while the proxy of ACHANGE, LEV, and BDOUT has no effect on the tendency of financial statement fraud.Key words: fraud, financial statement fraud, fraud triangle, pressure, opportunity, rationalization.